Mineral Resources of Mongolia as a Driving Force of the Country - Avirmed, Davaasuren (Mongolian Journal of International Affairs, 2021)
This article covers the concept of mineral resources, the definition of scientists as a factor in the development of the country, the use of natural resources in developed countries, as well as the focus on human development, the historical development of Mongolia’s mineral sector and the sector. For example, in 2009 the Government of Mongolia signed an agreement with the Canadian company “Ivanhoe Mines” to develop the “Oyu Tolgoi” copper and gold deposit, a list of strategically important mineral deposits announced by the Government of Mongolia, and mineral resources. The contribution of the sector to the social and economic development of Mongolia, the rapid development of countries with low mineral resources such as Southeast Korea, Taiwan, Hong Kong and Singapore, the geographical and climatic, foreign and domestic “Mongolia has a vision for sustainable development In order to achieve the goals set out in the “Mongolia 2030” and “VISION 2050” long-term vision of Mongolia’s development, it is necessary to implement development policies and planning tailored to its specific needs.